2024
DOI: 10.1021/jacs.3c12445
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 15N-Pyridines and Higher Mass Isotopologs via Zincke Imine Intermediates

Hillary M. H. Nguyen,
David C. Thomas,
Marie A. Hart
et al.

Abstract: Methods to incorporate stable radioisotopes are integral to pharmaceutical and agrochemical development. However, despite the prevalence of pyridines in candidate compounds, methods to incorporate 15 N atoms within their structures are limited.Here, we present a general approach to pyridine 15 N-labeling that proceeds via ring-opening to NTf-Zincke imines and then ringclosure with commercially available 15 NH 4 Cl salts. This process functions on a range of substituted pyridines, from simple building block-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This revealed that, while mildly effective at displacing triflamide, transfer of triflate to the alkyl amine was equally viable, reducing the overall likelihood for high 15 N isotopic enrichment through ANRORC displacement. It is worth noting that other groups concurrently investigated this mode of activation and were able to elegantly engineer its successful utilization for a similar 15 N isotopic labeling strategy. ,, In parallel, however, after much surveying of activation methods, a modified Zincke-type activation with tosylate 13 (see Scheme ) proved most effective in our hands across a relatively broad range of azine substrates …”
mentioning
confidence: 96%
“…This revealed that, while mildly effective at displacing triflamide, transfer of triflate to the alkyl amine was equally viable, reducing the overall likelihood for high 15 N isotopic enrichment through ANRORC displacement. It is worth noting that other groups concurrently investigated this mode of activation and were able to elegantly engineer its successful utilization for a similar 15 N isotopic labeling strategy. ,, In parallel, however, after much surveying of activation methods, a modified Zincke-type activation with tosylate 13 (see Scheme ) proved most effective in our hands across a relatively broad range of azine substrates …”
mentioning
confidence: 96%
“…Traditional early stage methods for introducing diverse isotopes often prove time-consuming and resource-intensive, encompassing multiple synthesis steps, harsh conditions, and expensive materials, presenting a significant challenge. However, recent advancements in late-stage approaches, particularly isotope exchange reactions involving hydrogen, carbon, fluorine, nitrogen, and sulfur, now allow for the direct labeling of the desired compound in a single step, effectively addressing challenges inherent in traditional methodologies.…”
mentioning
confidence: 99%